Expanding the biomass resource: sustainable oil production via fast pyrolysis of low input high diversity biomass and the potential integration of thermochemical and biological conversion routes. (1st September 2016) - Corton, J.; Donnison, I.S.; Patel, M.; Bühle, L.; Hodgson, E.; Wachendorf, M.; Bridgwater, A.; Allison, G.; Fraser, M.D.
Highlights: Biomass is generated during management of low input high diversity (LIHD) landscapes. Samples of LIHD biomass were subjected to fast pyrolysis. Demineralization through washing and pressing was associated with higher oil yields. Oil yields were within the range following fast pyrolysis of Miscanthus and Willow. Gross estimates of 4 × 10 5 tonne per year of oil could be displaced using Welsh LIHD biomass. Abstract: Waste biomass is generated during the conservation management of semi-natural habitats, and represents an unused resource and potential bioenergy feedstock that does not compete with food production. Thermogravimetric analysis was used to characterise a representative range of biomass generated during conservation management in Wales. Of the biomass types assessed, those dominated by rush ( Juncus effuses ) and bracken ( Pteridium aquilinum ) exhibited the highest and lowest volatile compositions respectively and were selected for bench scale conversion via fast pyrolysis. Each biomass type was ensiled and a sub-sample of silage was washed and pressed. Demineralization of conservation biomass through washing and pressing was associated with higher oil yields following fast pyrolysis. The oil yields were within the published range established for the dedicated energy crops miscanthus and willow. In order to examine the potential a multiple output energy system was developed with gross power production estimates following valorisation of the press fluid, char and oil. If used in multi fuel industrial burners the char and oil alone would displace 3.9 × 10 5 tonnes per year of No. 2 light oil using Welsh biomass from conservation management. Bioenergy and product development using these feedstocks could simultaneously support biodiversity management and displace fossil fuels, thereby reducing GHG emissions. Gross power generation predictions show good potential.